Real Estate Project: A feasibility study on a proposed Pureza Town Center: A three-storey commercial building located at Pureza, Santa Mesa Boulevard, Sampaloc, Manila. - Gloria, Shiara Mae A., Salalila, Mark Kenneth J., Santia, Nathaniel G., Zurbano, Gerard Paul T. 4 0 16; 5 (2024)
PROJECT NAME The project feasibility study will be entitled as A Feasibility Study of Pureza Town Center: A Three-Storey Commercial Building Located at Pureza, Santa Mesa Boulevard, Sampaloc, Manila. PROJECT DESCRIPTION The proposed project is a three-storey commercial building Pureza Town Central (PTC). The ground floor is composed of parking area, office, washrooms, utility room, mechanical room, a lift, and commercial spaces. On the second floor, it is composed of commercial units, a lift, and women's, men's, and PWD's toilet. While on the third floor is composed of an open space and a toilet for men, women, and for PWD. The said project aims to provide a cost-effective real estate project that will accommodate commercial activities and businesses and provide a space to lease. The development aims to provide a leasing space as mentioned in the description of the proposed project under the market study. Apart from this, the project will incorporate business opportunities within the area, with the goal of optimizing profit and space utilization through rentals. The project aims to ensure the full potential of the property's location to provide a profitable business for the lessee, in providing convenience to the surrounding neighborhood and its vicinity. The ground floor consisting of a lift and one office with a total size of 23.06 sqm. It serves as a centralized space for administrative tasks, meetings, and collaborative work. It provides a dedicated environment for employees to focus on their professional responsibilities, fostering productivity and efficient workflow. Additionally, having a designated office space enhances the professional image and organization of the business. The GF (Ground Floor) is also composed of a parking area, to provide safe, convenient, and organized spaces for parking vehicles. The project maximizes the number of parking spaces while ensuring easy maneuverability and pedestrian safety. Thus, it enhances customer satisfaction, boosts sales, and strengthens the project's reputation. Moreover, it showcases a business's commitment to safety, accessibility, and environmental responsibility. The parking area covers a 44.662 sqm with a total number of thirteen parking lot. Apart from this, a washroom is set with a quantity of three measuring in 5.63sqm, 7.55sqm, and 7.40sqm with a total cover of 20.58sqm. Having toilets and washroom are critical in mitigating possible public health risks. A utility room were also built with a measure of 12.41 sqm in total. This serves as a hub for essential services like electrical panels, HVAC systems, and plumbing. It helps centralize maintenance and repairs, ensuring efficient operation and easy access for technicians. With a total of 8.75sqm, mechanical room were also present covering a total of 8.75sqm in the GF (Ground Floor). It also provides a dedicated space for maintenance, repairs, and efficient operation, contributing to the overall functionality and longevity of the building's infrastructure. To utilize the space of the GF, two commercial space covering a 219.05sqm in total. The said spaces is good for its visibility, easy accessibility for customers, and potential for attractive storefront displays. The location and the vicinity that offers diverse services like public transportation and nearby facilities creating a foot traffic, hence making it a strategic choice for enhancing business presence and driving sales. The second-floor features a lift with a cover of 10.54sqm and three toilets covering an area of 25.06sqm, commercial units with a quantity of eight with a total coverage of 206.71sqm. By optimizing the available space and offering additional rental opportunities, the second floor is designed to cater to a diverse range of businesses, as outlined in the market study within the project proposal. This approach enhances the second floor's capacity to provide a varied business environment, offering customers a wide array of product or service choices. Simultaneously, it boosts the project's adaptability, making it more appealing to a broader spectrum of potential tenants. This inclusivity not only attracts a diverse range of businesses but also mitigates risks associated with economic fluctuations in specific industries. The diverse business environment created on the second floor serves to increase foot traffic and visibility for all tenants, making it an enticing destination for customers. Furthermore, from an investment standpoint, having a mix of tenant types contributes to a more stable and resilient income stream. In the event that one sector faces challenges, the project can still generate revenue from other thriving businesses, adding an additional layer of financial security. For the third floor, it has three toilets with a total of 25.06sqm, and an open space with a cover of 416.525sqm which is only available to be leased out as a whole floor. The proposed three-story commercial building, Pureza Town Central (PTC), aims to offer a cost-effective real estate solution, accommodating middle-class business owners with leasable spaces for various enterprises. The ground floor includes an office, parking area, toilet, utility room, mechanical room, and three units for rent. The emphasis on office space promotes productivity and professionalism, while the parking area prioritizes safety and convenience. The second and third floors provide diverse leasing opportunities, catering to different businesses, as outlined in the market study. The inclusion of toilets, units, stalls, and a dining table on the third floor creates a vibrant dining experience, attracting a broader customer base. The strategic design enhances adaptability, mitigates risks, and contributes to a stable income stream, making the project economically viable and supportive of local employment.
Feasibility Study: (Bachelor of Science in Real Estate Management) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2